Double-layer-structure polymer-based composite material for dielectric energy storage and preparation method of double-layer-structure polymer-based composite material

By adopting a double-layer structure design in polymer-based dielectric energy storage materials, using PEI and PVDF matrix composites respectively and introducing two-dimensional sheet fillers, the existing materials have low dielectric constant and low breakdown field strength and The problem of low energy storage efficiency has achieved the effect of high discharge energy storage density and high energy storage efficiency.

CN119459070AActive Publication Date: 2025-02-18HARBIN INST OF TECH
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202411617260.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-18
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

The existing polymer-based dielectric energy storage materials have low dielectric constant, low breakdown field strength and low energy storage efficiency, resulting in low discharge energy storage density and energy storage efficiency.

Method used

Using a double-layer structure polymer-based composite material, consisting of a PEI-based composite material film and a PVDF-based composite material film, two-dimensional sheet fillers are introduced to improve the dielectric properties of the material, and a double-layer structure is formed through a casting process to enhance the Interface effect.

Benefits of technology

High discharge energy storage density (Udis ≥ 20J/cm3) and high energy storage efficiency (η > 70%) were achieved, and the comprehensive energy storage performance was better than most of the polymer-based composite materials currently reported.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119459070A_ABST
    Figure CN119459070A_ABST
Patent Text Reader

Abstract

The invention discloses a double-layer structure polymer matrix composite material for dielectric energy storage and a preparation method thereof, and relates to a composite material for dielectric energy storage and a preparation method thereof. The problems that in the prior art, a polymer-based composite material is low in relative dielectric constant, not high in breakdown field strength and low in energy storage efficiency, and consequently the discharging energy storage density and the energy storage efficiency are low are solved. The material is a double-layer-structure polymer-based composite material composed of a PEI-based composite material film and a PVDF-based composite material film, the discharge energy storage density Udis is larger than or equal to 20 J / cm < 3 >, and the energy storage efficiency eta is larger than 70%. The method comprises the following steps: 1, preparing the two-dimensional flaky filler; 2, preparing a PEI-based composite material solution and a PVDF-based composite material solution; and 3, preparing the polymer-based composite material with the double-layer structure. The invention is used for the dielectric energy storage double-layer structure polymer matrix composite material and the preparation thereof.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a composite material for dielectric energy storage and a preparation method thereof. Background Art

[0002] In recent years, dielectric capacitors have played a vital role in advanced electronic power systems and energy storage devices due to their fast charge and discharge characteristics and excellent power density. Polymer-based dielectric capacitors are favored by researchers for their high electronic resistance, low mass, stable structure, and good flexibility. However, compared with batteries and supercapacitors, the low discharge energy storage density limits the wide application of polymer-based dielectric capacitors in the energy storage device market. To improve its discharge energy storage density (U dis ), the breakdown strength of its dielectric component must be increased (E b ) and relative dielectric constant (ε r )( Where ε0 is the dielectric constant of vacuum, which is 8.85×10 -12 F m -1 In this context, the polymer matrix is ​​filled with boron nitride nanosheets (BNNS), Ca2Nb3O 10 Two-dimensional dielectric materials such as MXene and montmorillonite (MMT) are an effective way to enhance the torsion of conductive pathways under large electric fields, thereby improving the E of composites. b Unfortunately, commonly used two-dimensional materials, such as BNNS ε r (~3-4) is relatively low, which is not conducive to improving the ε of the composite material r Moreover, its small size (~100nm) is not conducive to fully exerting the blocking effect of two-dimensional materials on space charge, resulting in the overall ε of the composite material after the introduction of these common two-dimensional materials. r No significant improvement, E b The increase is not obvious, which eventually leads to U dis In addition, the energy storage efficiency (η) of widely used single polymer matrix materials such as PVDF, PVDF-HFP and P(VDF-TrFE-CTFE) is very low, about 60%, which means that a lot of energy is lost and converted into heat, which is harmful to long-term operation. Therefore, it is necessary to develop materials with both high U dis and η dielectric energy storage materials remains a daunting challenge. Summary of the invention

[0003] The present invention aims to solve the problems of low relative dielectric constant, low breakdown field strength and low energy storage efficiency of polymer-based composite materials in the prior art, resulting in low discharge energy storage density and energy storage efficiency, and further provide a double-layer structured polymer-based composite material for dielectric energy storage with high discharge energy storage density and high energy storage efficiency and a preparation method thereof.

[0004] A double-layer structure polymer-based composite material for dielectric energy storage, which is a double-layer structure polymer-based composite material composed of a PEI-based composite material membrane and a PVDF-based composite material membrane;

[0005] The PEI-based composite material membrane is prepared from a PEI-based polymer and a two-dimensional flaky filler; the PVDF-based composite material membrane is prepared from a PVDF-based polymer and a two-dimensional flaky filler;

[0006] The PEI-based polymer is one or a combination of polyetherimide, polyimide and sulfide polyetherimide;

[0007] The PVDF-based polymer is one or a combination of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene and terpolymer P (VDF-TrFE-CTFE);

[0008] The two-dimensional sheet filler is Na 0.5 Bi 4.5 Ti4O 15 、Bi4Ti3O 12 and SrBi2Ta2O9 or a combination of several thereof;

[0009] The two-dimensional flaky filler has a diameter of 0.5 μm to 5 μm; the two-dimensional flaky filler in the PEI-based composite material membrane accounts for 0.1% to 2.0% of the mass of the PEI-based polymer; the two-dimensional flaky filler in the PVDF-based composite material membrane accounts for 0.1% to 2.0% of the mass of the PVDF-based polymer;

[0010] The discharge energy storage density U of the double-layer structure polymer-based composite material for dielectric energy storage dis ≥20J / cm 3 , energy storage efficiency η>70%.

[0011] A method for preparing a double-layer structure polymer-based composite material for dielectric energy storage is carried out according to the following steps:

[0012] 1. Preparation of two-dimensional flake fillers:

[0013] Weighing raw materials according to the stoichiometric ratio of the chemical formula of the two-dimensional flaky filler, and weighing NaCl according to the mass ratio of the raw materials to the molten salt of 1: (1.5-15); ball-milling the raw materials and NaCl to obtain a mixture, calcining the mixture at a temperature of 800° C. to 1050° C. for 1 h to 8 h, and finally washing and drying to obtain a two-dimensional flaky filler;

[0014] The two-dimensional sheet filler has a sheet diameter of 0.5 μm to 5 μm; the two-dimensional sheet filler is Na0.5 Bi 4.5 Ti4O 15 、Bi4Ti3O 12 and SrBi2Ta2O9 or a combination of several thereof;

[0015] 2. Preparation of PEI-based composite material solution and PVDF-based composite material solution:

[0016] A PEI-based composite material solution and a PVDF-based composite material solution are prepared respectively by using a PEI-based polymer, a PVDF-based polymer, a two-dimensional sheet filler and N-methylpyrrolidone;

[0017] The PEI-based polymer is one or a combination of polyetherimide, polyimide and sulfide polyetherimide;

[0018] The PVDF-based polymer is one or a combination of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene and terpolymer P (VDF-TrFE-CTFE);

[0019] The two-dimensional flaky filler in the PEI-based composite material solution accounts for 0.1% to 2.0% of the mass of the PEI-based polymer; the two-dimensional flaky filler in the PVDF-based composite material solution accounts for 0.1% to 2.0% of the mass of the PVDF-based polymer;

[0020] 3. Preparation of double-layer structure polymer-based composite materials:

[0021] The PEI-based composite material solution is cast on a substrate and vacuum dried to obtain a PEI-based composite material membrane, and then the PVDF-based composite material solution is cast on the PEI-based composite material membrane and vacuum dried, and finally the formed double-layer structure polymer-based composite material is removed from the substrate, thereby completing the preparation method of the double-layer structure polymer-based composite material for dielectric energy storage.

[0022] Principle: The present invention selects two PVDF-based polymers with different energy storage properties (high ε r ) and PEI-based polymers (high E b and η) as the matrix, the two-dimensional sheet filler as the powder filler, and the double-layer structure design are combined to invent a polymer-based composite material with both high discharge energy storage density and high energy storage efficiency. Specifically, an appropriate amount of high ε is introduced into the PVDF-based polymer and the PEI-based polymer. r On the one hand, the two-dimensional sheet filler has a high ε r , which can improve the ε of the composite material rOn the other hand, the two-dimensional sheet filler can give full play to its blocking effect on the space charge applied on the surface as a two-dimensional material, and can effectively block the charge from passing along the direction perpendicular to the plane, thereby improving the E of the composite material. b In addition, the two improved composite materials are combined through a layer-by-layer tape-casting process, and a large number of electron deep traps are formed at the interface by using the interface effect to bind the charge through, thereby improving the material's breakdown resistance, making the E of the double-layer structure polymer-based composite material b Further improve, thereby increasing the discharge energy storage density U dis , optimize η.

[0023] Beneficial effects of the present invention:

[0024] Based on the synergistic regulation strategy of the space charge blocking effect of two-dimensional materials and the charge binding effect of the double-layer structure interface effect, a polymer-based composite material with both high discharge energy storage density and high energy storage efficiency is prepared. The discharge energy storage density U dis ≥20J / cm 3 , energy storage efficiency η>70%, and the comprehensive energy storage performance is better than most polymer-based composite materials reported so far. In addition, under the conditions of resistance R of 300Ω and electric field of 3000kV / cm, the discharge rate t 0.9 ≤50ns, power density P D More than 50MW / cm 3 .

[0025] The preparation process of the present invention is simple and efficient, which is conducive to industrial mass production. It provides a design and preparation idea for the continued research and development of polymer-based energy storage capacitors with high energy storage density, excellent energy storage stability and a wide practical temperature range. At the same time, the polymer-based capacitor shows great application potential as an energy storage element in the integrated, lightweight and miniaturized applications of pulse power devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The two-dimensional sheet Na prepared in step 1 of Example 1 0.5 Bi 4.5 Ti4O 15 Microscopic morphology of filler;

[0027] Figure 2 Hysteresis loop diagrams under breakdown field strength, (a) P(VDF-HFP) film and NBT-P(VDF-HFP) film, (b) PEI film and NBT-PEI film;

[0028] Figure 3The morphology and element energy distribution diagrams of the double-layer structure polymer-based composite material for dielectric energy storage prepared in Example 1, (a) cross-sectional microscopic morphology, (b) energy distribution diagram of characteristic element F of NBT-P (VDF-HFP) film, (c) energy distribution diagram of characteristic element O of NBT-PEI film;

[0029] Figure 4 The hysteresis loop of the double-layer structure polymer-based composite material for dielectric energy storage prepared in Example 1 under the breakdown field strength;

[0030] Figure 5 This is a charge and discharge rate diagram of the double-layer structure polymer-based composite material for dielectric energy storage prepared in Example 1;

[0031] Figure 6 The hysteresis loop of the double-layer structure polymer-based composite material for dielectric energy storage prepared in Example 2 under the breakdown field strength;

[0032] Figure 7 This is the hysteresis loop of the double-layer structure polymer-based composite material for dielectric energy storage prepared in Example 3 under the breakdown field strength. DETAILED DESCRIPTION

[0033] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any combination of the specific implementation modes.

[0034] Specific implementation method 1: This implementation method is a double-layer structure polymer-based composite material for dielectric energy storage, which is a double-layer structure polymer-based composite material composed of a PEI-based composite film and a PVDF-based composite film;

[0035] The PEI-based composite material membrane is prepared from a PEI-based polymer and a two-dimensional flaky filler; the PVDF-based composite material membrane is prepared from a PVDF-based polymer and a two-dimensional flaky filler;

[0036] The PEI-based polymer is one or a combination of polyetherimide, polyimide and sulfide polyetherimide;

[0037] The PVDF-based polymer is one or a combination of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene and terpolymer P (VDF-TrFE-CTFE);

[0038] The two-dimensional sheet filler is Na 0.5 Bi 4.5 Ti4O 15 、Bi4Ti3O 12 and SrBi2Ta2O9 or a combination of several thereof;

[0039] The two-dimensional flaky filler has a diameter of 0.5 μm to 5 μm; the two-dimensional flaky filler in the PEI-based composite material membrane accounts for 0.1% to 2.0% of the mass of the PEI-based polymer; the two-dimensional flaky filler in the PVDF-based composite material membrane accounts for 0.1% to 2.0% of the mass of the PVDF-based polymer;

[0040] The discharge energy storage density U of the double-layer structure polymer-based composite material for dielectric energy storage dis ≥20J / cm 3 , energy storage efficiency η>70%.

[0041] Beneficial effects of this specific implementation method:

[0042] This specific implementation is based on the synergistic regulation strategy of the space charge blocking effect of two-dimensional materials and the charge binding effect of the double-layer structure interface effect, and a polymer-based composite material with both high discharge energy storage density and high energy storage efficiency is prepared. The discharge energy storage density U dis ≥20J / cm 3 , energy storage efficiency η>70%, and the comprehensive energy storage performance is better than most polymer-based composite materials reported so far. In addition, under the conditions of resistance R of 300Ω and electric field of 3000kV / cm, the discharge rate t 0.9 ≤50ns, power density P D More than 50MW / cm 3 .

[0043] The preparation process of this specific embodiment is simple and efficient, which is conducive to industrial mass production. It provides a design and preparation idea for the continued research and development of polymer-based energy storage capacitors with high energy storage density, excellent energy storage stability and a wide practical temperature range. At the same time, the polymer-based capacitor shows great application potential as an energy storage element in the integrated, lightweight and miniaturized applications of pulse power devices.

[0044] Specific embodiment 2: This embodiment is different from specific embodiment 1 in that: the thickness ratio of the PEI-based composite material membrane to the PVDF-based composite material membrane is 1:(0.2-3.0); the sheet diameter of the two-dimensional flaky filler is 1 μm-2 μm; the two-dimensional flaky filler in the PEI-based composite material membrane accounts for 0.25%-1.0% of the mass of the PEI-based polymer; the two-dimensional flaky filler in the PVDF-based composite material membrane accounts for 0.25%-1.0% of the mass of the PVDF-based polymer. Others are the same as specific embodiment 1.

[0045] Specific embodiment 3: A method for preparing a double-layer structure polymer-based composite material for dielectric energy storage, which is completed by the following steps:

[0046] 1. Preparation of two-dimensional flake fillers:

[0047] Weighing raw materials according to the stoichiometric ratio of the chemical formula of the two-dimensional flaky filler, and weighing NaCl according to the mass ratio of the raw materials to the molten salt of 1: (1.5-15); ball-milling the raw materials and NaCl to obtain a mixture, calcining the mixture at a temperature of 800° C. to 1050° C. for 1 h to 8 h, and finally washing and drying to obtain a two-dimensional flaky filler;

[0048] The two-dimensional sheet filler has a sheet diameter of 0.5 μm to 5 μm; the two-dimensional sheet filler is Na 0.5 Bi 4.5 Ti4O 15 、Bi4Ti3O 12 and SrBi2Ta2O9 or a combination of several thereof;

[0049] 2. Preparation of PEI-based composite material solution and PVDF-based composite material solution:

[0050] A PEI-based composite material solution and a PVDF-based composite material solution are prepared respectively by using a PEI-based polymer, a PVDF-based polymer, a two-dimensional sheet filler and N-methylpyrrolidone;

[0051] The PEI-based polymer is one or a combination of polyetherimide, polyimide and sulfide polyetherimide;

[0052] The PVDF-based polymer is one or a combination of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene and terpolymer P (VDF-TrFE-CTFE);

[0053] The two-dimensional flaky filler in the PEI-based composite material solution accounts for 0.1% to 2.0% of the mass of the PEI-based polymer; the two-dimensional flaky filler in the PVDF-based composite material solution accounts for 0.1% to 2.0% of the mass of the PVDF-based polymer;

[0054] 3. Preparation of double-layer structure polymer-based composite materials:

[0055] The PEI-based composite material solution is cast on a substrate and vacuum dried to obtain a PEI-based composite material membrane, and then the PVDF-based composite material solution is cast on the PEI-based composite material membrane and vacuum dried, and finally the formed double-layer structure polymer-based composite material is removed from the substrate, thereby completing the preparation method of the double-layer structure polymer-based composite material for dielectric energy storage.

[0056] In step three of this specific implementation, since the PEI-based polymer is a thermosetting polymer and is insoluble in the PVDF-based composite material solution, the PVDF-based composite material solution is cast on the PEI-based composite material membrane as a top membrane, and the PEI-based composite material membrane is used as a bottom membrane.

[0057] Specific implementation method 4: This implementation method is different from specific implementation method 3 in that the purity of the raw materials and NaCl in step 1 is ≥ 99.0%. Other aspects are the same as those of specific implementation method 3.

[0058] Specific embodiment 5: This embodiment is different from specific embodiment 3 or 4 in that the ball milling mixing described in step 1 is specifically carried out according to the following steps: using ethanol as the ball milling medium, at a rotation speed of 800r / min to 1200r / min, ball milling mixing for 12h to 24h. Other aspects are the same as specific embodiment 3 or 4.

[0059] Specific embodiment 6: This embodiment is different from any one of specific embodiments 3 to 5 in that: the concentration of the PEI-based polymer in the PEI-based composite material solution described in step 2 is 0.1 g / mL to 0.2 g / mL; the concentration of the PVDF-based polymer in the PVDF-based composite material solution described in step 2 is 0.1 g / mL to 0.2 g / mL. The rest is the same as specific embodiments 3 to 5.

[0060] Specific embodiment 7: This embodiment is different from any one of specific embodiments 3 to 6 in that: in step 2, PEI-based polymer, PVDF-based polymer, two-dimensional sheet filler and N-methylpyrrolidone are used to prepare PEI-based composite material solution and PVDF-based composite material solution respectively, which is specifically carried out according to the following steps:

[0061] ① Add PEI-based polymer into N-methylpyrrolidone and stir until the particles are completely dissolved to obtain a PEI-based polymer solution;

[0062] ② Add the PVDF-based polymer into N-methylpyrrolidone and stir until the particles are completely dissolved to obtain a PVDF-based polymer solution;

[0063] ③ Under the condition of power of 500W to 700W, add the two-dimensional flake filler into N-methylpyrrolidone and ultrasonically disperse for 10min to 20min to obtain a two-dimensional flake filler dispersion;

[0064] ④ Under the condition of a rotation speed of 1000r / min to 1500r / min, the PEI-based polymer solution and the two-dimensional flaky filler dispersion are mixed for 10h to 14h to obtain a PEI-based composite material solution; under the condition of a rotation speed of 1000r / min to 1500r / min, the PVDF-based polymer solution and the two-dimensional flaky filler dispersion are mixed for 10h to 14h to obtain a PVDF-based composite material solution. The rest is the same as the specific embodiments three to six.

[0065] The purpose of ultrasonic dispersion in step ③ of this specific implementation method is to fully separate the two-dimensional flake fillers and avoid agglomeration.

[0066] Specific embodiment 8: This embodiment is different from any one of specific embodiments 3 to 7 in that the casting in step 3 is performed by using a casting machine at a casting speed of 2 cm / s to 4 cm / s. The rest is the same as specific embodiments 3 to 7.

[0067] Specific embodiment 9: This embodiment is different from any one of specific embodiments 3 to 8 in that: the diameter of the two-dimensional flaky filler described in step 1 is 1 μm to 2 μm; the two-dimensional flaky filler in the PEI-based composite material solution described in step 2 accounts for 0.25% to 1.0% of the mass of the PEI-based polymer; the two-dimensional flaky filler in the PVDF-based composite material solution described in step 2 accounts for 0.25% to 1.0% of the mass of the PVDF-based polymer; the thickness ratio of the PEI-based composite film to the PVDF-based composite film described in step 3 is 1:(0.2 to 3.0). Others are the same as specific embodiments 3 to 8.

[0068] Specific embodiment 10: This embodiment is different from any one of specific embodiments 3 to 9 in that the thickness of the double-layer structure polymer-based composite material prepared in step 3 is 7 μm to 10 μm. The rest is the same as specific embodiments 3 to 9.

[0069] The following examples are used to verify the beneficial effects of the present invention:

[0070] Embodiment 1:

[0071] A method for preparing a double-layer structure polymer-based composite material for dielectric energy storage is carried out according to the following steps:

[0072] 1.2D Na flakes 0.5 Bi 4.5 Ti4O 15 Preparation of filler:

[0073] According to Na 0.5 Bi 4.5 Ti4O 15Na2CO3, Bi2O3 and TiO2 were weighed as raw materials in a stoichiometric ratio, and NaCl was weighed at a mass ratio of raw materials to molten salt of 1:15; ethanol was used as a ball milling medium, and the raw materials and NaCl were ball milled for 24 hours at a speed of 900 r / min to obtain a mixture, which was calcined at a temperature of 850°C for 1 hour, and finally washed and dried to obtain a two-dimensional sheet of Na 0.5 Bi 4.5 Ti4O 15 filler;

[0074] The two-dimensional sheet Na 0.5 Bi 4.5 Ti4O 15 The filler sheet diameter is 1 μm to 2 μm;

[0075] 2. Preparation of NBT-PEI solution and NBT-P (VDF-HFP) solution:

[0076] ① Add polyetherimide to N-methylpyrrolidone and stir until the particles are completely dissolved to obtain a PEI solution;

[0077] ② Add polyvinylidene fluoride-hexafluoropropylene into N-methylpyrrolidone and stir until the particles are completely dissolved to obtain P(VDF-HFP) solution;

[0078] ③ Under the condition of 600W power, the two-dimensional sheet Na 0.5 Bi 4.5 Ti4O 15 The filler was added into N-methylpyrrolidone and ultrasonically dispersed for 20 min to obtain a two-dimensional flake NBT dispersion;

[0079] ④ At a rotation speed of 1500 r / min, the PEI solution was mixed with the two-dimensional NBT dispersion for 12 hours to obtain an NBT-PEI solution; at a rotation speed of 1500 r / min, the P (VDF-HFP) solution was mixed with the two-dimensional NBT dispersion for 12 hours to obtain an NBT-P (VDF-HFP) solution;

[0080] The concentration of polyetherimide in the NBT-PEI solution is 0.16 g / mL; the concentration of polyvinylidene fluoride-hexafluoropropylene in the NBT-P (VDF-HFP) solution is 0.16 g / mL; the concentration of two-dimensional sheet Na in the NBT-PEI solution is 0.16 g / mL. 0.5 Bi 4.5 Ti4O 15 The filler accounts for 0.75% of the mass of the polyetherimide; the two-dimensional sheet Na 0.5 Bi 4.5 Ti4O15 The filler accounts for 0.75% of the mass of polyvinylidene fluoride-hexafluoropropylene;

[0081] 3. Preparation of double-layer NBT-PEI / NBT-P (VDF-HFP) composite materials:

[0082] Under the condition of a casting speed of 3 cm / s, a NBT-PEI solution is cast on a glass substrate using a casting machine, and vacuum dried for 12 hours at a temperature of 70°C to obtain an NBT-PEI film, and then, under the condition of a casting speed of 3 cm / s, a NBT-P (VDF-HFP) solution is cast on the NBT-PEI film using a casting machine, and vacuum dried for 12 hours at a temperature of 70°C, and finally the formed double-layer structure NBT-PEI / NBT-P (VDF-HFP) composite material is removed from the substrate, which is a double-layer structure polymer-based composite material for dielectric energy storage;

[0083] The purity of Na2CO3 described in step 1 is 99.5%; the purity of Bi2O3 described in step 1 is ≥99.9%; the purity of TiO2 described in step 1 is ≥99.0%; the purity of NaCl described in step 1 is ≥99.5%.

[0084] The double-layer structure polymer-based composite material for dielectric energy storage prepared above is a double-layer structure polymer-based composite material with a thickness of 8 μm composed of NBT-PEI film and NBT-P (VDF-HFP) film; the thickness ratio of the NBT-PEI film to the NBT-P (VDF-HFP) film is 0.7:0.3;

[0085] The two-dimensional sheet Na 0.5 Bi 4.5 Ti4O 15 The filler sheet diameter is 1 μm to 2 μm; the two-dimensional sheet Na 0.5 Bi 4.5 Ti4O 15 The filler accounts for 0.75% of the mass of the polyetherimide; the two-dimensional sheet Na 0.5 Bi 4.5 Ti4O 15 The filler accounts for 0.75% of the mass of polyvinylidene fluoride-hexafluoropropylene;

[0086] The double-layer structure polymer-based composite material for dielectric energy storage prepared in Example 1 was covered with Au electrodes with a diameter of 2 mm on both sides to measure the electrical properties: the breakdown electric field E b is 8283kV / cm, and the discharge energy storage density Udis =25.0J / cm 3 , energy storage efficiency η = 81.2%; under the conditions of resistance R of 300Ω and electric field of 3000kV / cm, the discharge rate t of the double-layer structure polymer-based composite material for dielectric energy storage 0.9 is 46.6ns, power density P D 62.2MW / cm 3 .

[0087] Figure 1 The two-dimensional sheet Na prepared in step 1 of Example 1 0.5 Bi 4.5 Ti4O 15 Microscopic morphology of the filler; as can be seen from the figure, the two-dimensional flake NBT prepared by the molten salt method has a regular shape and a size of about 1μm to 2μm.

[0088] Using the casting method of step 3 of Example 1, PEI film, P(VDF-HFP) film, NBT-PEI film and NBT-P(VDF-HFP) film were separately prepared on the substrate, wherein the thickness of the PEI film, P(VDF-HFP) film, NBT-PEI film and NBT-P(VDF-HFP) film was 8 μm, and Au electrodes with a diameter of 2 mm were covered on both sides of the film for measuring electrical properties;

[0089] Figure 2 The hysteresis loop diagram under the breakdown field strength is (a) P(VDF-HFP) film and NBT-P(VDF-HFP) film, (b) PEI film and NBT-PEI film. It can be seen from the figure that after the introduction of two-dimensional sheet NBT, the breakdown field strength E b The breakdown field strength of NBT-PEI film was increased from 4986 kV / cm to 6084 kV / cm. b From 5467kV / cm to 7484kV / cm. In addition, due to the higher ε r The polarization strength of NBT-PEI film and NBT-P (VDF-HFP) film under the same field strength is also improved. This shows that the two-dimensional sheet NBT is very important for improving the E b and polarization intensity play an important role. Therefore, the energy storage density is calculated by the following formula:

[0090]

[0091] Among them U dis is the discharge energy storage density, in J / cm 3 ; U tot is the total energy storage density, in J / cm 3 ; η is the energy storage efficiency; Pmax is the maximum polarization intensity, in μC / cm 2 ;P r is the residual polarization intensity, unit is μC / cm 2 ; E is the external electric field, unit kV / cm. It can be calculated that after the introduction of two-dimensional sheet NBT, the discharge energy storage density U of NBT-P (VDF-HFP) film dis From 9.8J / cm 3 Increased to 15.5J / cm 3 , the energy storage efficiency η increased from 60.7% to 62.4%; the discharge energy storage density U of NBT-PEI film dis From 8.2J / cm 3 Increased to 16.7J / cm 3 , the energy storage efficiency η increased from 90.1% to 92.3%; this shows that the introduction of NBT plays an important role in improving the overall energy storage performance of the composite material.

[0092] Figure 3 The morphology and element energy distribution diagrams of the double-layer structure polymer-based composite material for dielectric energy storage prepared in Example 1, (a) cross-sectional microscopic morphology, (b) energy distribution diagram of characteristic element F of NBT-P (VDF-HFP) film, (c) energy distribution diagram of characteristic element O of NBT-PEI film. Figure 3 (a) It can be seen that NBT-P (VDF-HFP) and NBT-PEI in the double-layer composite material are located in the upper and lower layers of the figure respectively, and the two layers of the composite material are tightly combined without any gaps. Figure 3 (b) and (c) show that the characteristic element F representing the NBT-P (VDF-HFP) layer and the characteristic element O representing NBT-PEI are evenly dispersed in each layer, proving that the quality of the entire double-layer structure is uniform, providing a basis for its superior energy storage performance.

[0093] Figure 4 The hysteresis loop of the double-layer structure polymer-based composite material for dielectric energy storage prepared in Example 1 under the breakdown field strength; As can be seen from the figure, the breakdown field strength E of the double-layer structure NBT-PEI / NBT-P (VDF-HFP) composite material b It is 8283kV / cm. The discharge energy storage density U dis 25.0J / cm 3 , the energy storage efficiency η is 81.2%.

[0094] Figure 5 The charge and discharge rate diagram of the double-layer structure polymer-based composite material for dielectric energy storage prepared in Example 1; it can be seen from the figure that under the conditions of resistance R of 300Ω and electric field of 3000kV / cm, the discharge rate t 0.9is 46.6ns, power density P D 62.2MW / cm 3 .

[0095] Embodiment 2: This embodiment is different from Embodiment 1 in that the thickness ratio of the NBT-PEI film to the NBT-P (VDF-HFP) film is 0.5:0.5. The rest is the same as Embodiment 1.

[0096] The double-layer structure polymer-based composite material for dielectric energy storage prepared in Example 2 was covered with Au electrodes with a diameter of 2 mm on both sides to measure the electrical properties: Figure 6 The hysteresis loop of the double-layer structure polymer-based composite material for dielectric energy storage prepared in Example 2 under the breakdown field strength; the breakdown electric field E of the double-layer structure polymer-based composite material for dielectric energy storage b is 7791kV / cm, and the discharge energy storage density U dis =23.6J / cm 3 , energy storage efficiency η = 76.1%.

[0097] Embodiment 3: This embodiment is different from Embodiment 1 in that the thickness ratio of the NBT-PEI film to the NBT-P (VDF-HFP) film is 0.3:0.7. Other aspects are the same as Embodiment 1.

[0098] The double-layer structure polymer-based composite material for dielectric energy storage prepared in Example 3 was covered with Au electrodes with a diameter of 2 mm on both sides to measure the electrical properties: Figure 7 The hysteresis loop of the double-layer structure polymer-based composite material for dielectric energy storage prepared in Example 3 under the breakdown field strength; the breakdown electric field E of the double-layer structure polymer-based composite material for dielectric energy storage b is 7082kV / cm, and the discharge energy storage density U dis =21.5J / cm 3 , energy storage efficiency η = 73.4%.

Claims

1. A double-layer structure polymer-based composite material for dielectric energy storage, characterized in that It is a double-layer structure polymer-based composite material composed of a PEI-based composite film and a PVDF-based composite film; The PEI-based composite material membrane is prepared from a PEI-based polymer and a two-dimensional flaky filler; the PVDF-based composite material membrane is prepared from a PVDF-based polymer and a two-dimensional flaky filler; The PEI-based polymer is one or a combination of polyetherimide, polyimide and sulfide polyetherimide; The PVDF-based polymer is one or a combination of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene and terpolymer P (VDF-TrFE-CTFE); The two-dimensional sheet filler is Na 0.5 Bi 4.5 Ti4O 15 、Bi4Ti3O 12 and SrBi2Ta2O9 or a combination of several thereof; The two-dimensional flaky filler has a diameter of 0.5 μm to 5 μm; the two-dimensional flaky filler in the PEI-based composite material membrane accounts for 0.1% to 2.0% of the mass of the PEI-based polymer; the two-dimensional flaky filler in the PVDF-based composite material membrane accounts for 0.1% to 2.0% of the mass of the PVDF-based polymer; The discharge energy storage density U of the double-layer structure polymer-based composite material for dielectric energy storage dis ≥20J / cm 3 , energy storage efficiency η>70%.

2. A double-layer structure polymer-based composite material for dielectric energy storage according to claim 1, characterized in that The thickness ratio of the PEI-based composite material membrane to the PVDF-based composite material membrane is 1:(0.2-3.0); the diameter of the two-dimensional flaky filler is 1 μm-2 μm; the two-dimensional flaky filler in the PEI-based composite material membrane accounts for 0.25%-1.0% of the mass of the PEI-based polymer; the two-dimensional flaky filler in the PVDF-based composite material membrane accounts for 0.25%-1.0% of the mass of the PVDF-based polymer.

3. A method for preparing a double-layer structure polymer-based composite material for dielectric energy storage according to claim 1, characterized in that It is carried out in the following steps:

1. Preparation of two-dimensional flake fillers: Weighing raw materials according to the stoichiometric ratio of the chemical formula of the two-dimensional flaky filler, and weighing NaCl according to the mass ratio of the raw materials to the molten salt of 1: (1.5-15); ball-milling the raw materials and NaCl to obtain a mixture, calcining the mixture at a temperature of 800° C. to 1050° C. for 1 h to 8 h, and finally washing and drying to obtain a two-dimensional flaky filler; The two-dimensional sheet filler has a sheet diameter of 0.5 μm to 5 μm; the two-dimensional sheet filler is Na 0.5 Bi 4.5 Ti4O 15 、Bi4Ti3O 12 and SrBi2Ta2O9 or a combination of several thereof; 2. Preparation of PEI-based composite material solution and PVDF-based composite material solution: A PEI-based composite material solution and a PVDF-based composite material solution are prepared respectively by using a PEI-based polymer, a PVDF-based polymer, a two-dimensional sheet filler and N-methylpyrrolidone; The PEI-based polymer is one or a combination of polyetherimide, polyimide and sulfide polyetherimide; The PVDF-based polymer is one or a combination of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene and terpolymer P (VDF-TrFE-CTFE); The two-dimensional flaky filler in the PEI-based composite material solution accounts for 0.1% to 2.0% of the mass of the PEI-based polymer; the two-dimensional flaky filler in the PVDF-based composite material solution accounts for 0.1% to 2.0% of the mass of the PVDF-based polymer; 3. Preparation of double-layer structure polymer-based composite materials: The PEI-based composite material solution is cast on a substrate and vacuum dried to obtain a PEI-based composite material membrane, and then the PVDF-based composite material solution is cast on the PEI-based composite material membrane and vacuum dried, and finally the formed double-layer structure polymer-based composite material is removed from the substrate, thereby completing the preparation method of the double-layer structure polymer-based composite material for dielectric energy storage.

4. The method for preparing a double-layer structure polymer-based composite material for dielectric energy storage according to claim 3, characterized in that The purity of the raw materials and NaCl described in step 1 is ≥ 99.0%.

5. The method for preparing a double-layer structure polymer-based composite material for dielectric energy storage according to claim 3, characterized in that The ball milling mixing described in step 1 is specifically carried out according to the following steps: using ethanol as the ball milling medium, ball milling mixing is performed for 12 hours to 24 hours at a rotation speed of 800 r / min to 1200 r / min.

6. The method for preparing a double-layer structure polymer-based composite material for dielectric energy storage according to claim 3, characterized in that The concentration of the PEI-based polymer in the PEI-based composite material solution described in step 2 is 0.1 g / mL to 0.2 g / mL; the concentration of the PVDF-based polymer in the PVDF-based composite material solution described in step 2 is 0.1 g / mL to 0.2 g / mL.

7. The method for preparing a double-layer structure polymer-based composite material for dielectric energy storage according to claim 3, characterized in that In step 2, a PEI-based composite material solution and a PVDF-based composite material solution are prepared respectively using a PEI-based polymer, a PVDF-based polymer, a two-dimensional sheet filler and N-methylpyrrolidone, and the steps are specifically as follows: ① Add PEI-based polymer into N-methylpyrrolidone and stir until the particles are completely dissolved to obtain a PEI-based polymer solution; ② Add the PVDF-based polymer into N-methylpyrrolidone and stir until the particles are completely dissolved to obtain a PVDF-based polymer solution; ③ Under the condition of power of 500W to 700W, add the two-dimensional flake filler into N-methylpyrrolidone and ultrasonically disperse for 10min to 20min to obtain a two-dimensional flake filler dispersion; ④ Under the condition of a rotation speed of 1000r / min~1500r / min, the PEI-based polymer solution and the two-dimensional flaky filler dispersion are mixed for 10h~14h to obtain a PEI-based composite material solution; under the condition of a rotation speed of 1000r / min~1500r / min, the PVDF-based polymer solution and the two-dimensional flaky filler dispersion are mixed for 10h~14h to obtain a PVDF-based composite material solution.

8. The method for preparing a double-layer structure polymer-based composite material for dielectric energy storage according to claim 3, characterized in that The casting described in step 3 is specifically performed by using a casting machine at a casting speed of 2 cm / s to 4 cm / s.

9. The method for preparing a double-layer structure polymer-based composite material for dielectric energy storage according to claim 3, characterized in that The diameter of the two-dimensional flaky filler described in step one is 1 μm to 2 μm; the two-dimensional flaky filler in the PEI-based composite material solution described in step two accounts for 0.25% to 1.0% of the mass of the PEI-based polymer; the two-dimensional flaky filler in the PVDF-based composite material solution described in step two accounts for 0.25% to 1.0% of the mass of the PVDF-based polymer; the thickness ratio of the PEI-based composite film to the PVDF-based composite film described in step three is 1:(0.2 to 3.0).

10. The method for preparing a double-layer structure polymer-based composite material for dielectric energy storage according to claim 3, characterized in that The thickness of the double-layer structure polymer-based composite material prepared in step three is 7 μm to 10 μm.

Citation Information

Patent Citations

  • Laminated-structure polymer-based dielectric energy-storage composite material and preparation method thereof

    CN104044318A

  • High dielectric property and low loss sheet-shaped barium titanate base / polymer composite material and preparation method thereof

    CN104530616A

  • Electric energy storage dielectric ceramic / polymer composite material and preparing method thereof

    CN105086297A

  • Polymer-based composite dielectric material, preparation method thereof and energy storage device

    CN110713618A

  • Sandwich-structure PVDF high-energy-storage-density composite film material and preparation method thereof

    CN110948981A